Clarão que seduz? As aprendizagens e os saberes docentes nas escolas estaduais de educação profissional do Ceará - Vasconcelos, Maria Aurilene de Deus Moreira (2021)
This research’s main objective is to understand how teachers from Vocational Education State Schools develop and integrate their knowledge in their teaching practice. For that end, it intended to reconstruct the process of constituting the teaching practice of a group of teachers in the material and historical context in which it takes place, to understand and analyze the explicit and implicit knowledge of practice, produced and/or appropriated by them throughout their personal and professional lives. For this challenge, an impersonal methodology cannot be chosen, so I found in the research of qualitative approach, methodology of more sensitive character, the necessary epistemological theoretical support to ground the investigation. Through it, I was able to better integrate myself in the world of my research subjects, using more subjective and comprehensive actions and interpretations to understand the knowledge developed by them, with their material and subjective questions. Given the wealth of alternatives and possibilities that a qualitative approach presents, the use of the focus group technique was also defined to achieve the objectives outlined here. The research results demonstrated that the interviewees develop different knowledge and learning throughout their careers. It was possible to identify their disciplinary, curricular, pedagogical, and experiential knowledge, from the educational sciences, all from different sources, from their initial or continuing education, from their “meetings”, from social practices. The study also revealed that teachers maintain a closer relationship with the knowledge of experience than with scientific knowledge. They acknowledge the relevance of the latter, however, when faced with challenging everyday situations, they seek the experiential knowledge, developed in the school routine, sometimes learned with the students themselves or with their peers. The investigation also made it possible to reflect on how the pedagogical action is influenced by personal experiences and the teaching professional career.